Increased resource exploitation through intercropping with cassava - Wilson, G.F.; Lawson, T.L. (1982)
Yields of 1st season maize grown at 30 000 and 40 000 plants/ha were not adversely affected when cassava was interplanted at 10 000 plants/ha. The use of resources based on measurements of photosynthetic efficiency showed that maize reached higher photosynthetic peaks than cassava, and intercrop competition was most severe at this time. Tuberization of cassava occurred during the long postcompetition growth period, allowing for high yields. It was concluded that cassava was an ideal crop for exploiting uncertain tropical environments.